(untitled) (Conference Zone, 2022)
There are a huge number of file formats that describe 3D objects and scenes. But most of them were created by individual firms and developers. Each of them had specific limitations and was used to solve problems in rather narrow areas. Therefore, there was a constant urgent need to transfer files from one format to another in order to use previously obtained models for new tasks. This article analyzes the traditional and non-traditional ways of creating electronic learning resources.